Investigation of the energy recovery in the burners of the ceramic factory kiln. (July 2018) - Caglayan, Hasan; Caliskan, Hakan
Abstract: The energy costs are increasing day after day and it effects the compete in the ceramic sector. As a result, energy recovery projects becomes important. Each energy-consuming process is re-examined and waste heat recovery projects are being developed to minimize the total consumption in the ceramic factory. In this study, energy saving is achieved by using air in the cooling section of the kiln (148°C) instead of the ambient air for the burners of kiln. The air is used in the kilns in which natural gas is consumed mostly. It is found that 4.7% natural gas savings can be achieved for 148°C air (improved system) that is taken from the cooling section of the kiln. And the improved system payback period is determined as 10 months by using Net Present Value (NPV) method. The natural gas saving may be increased to 8%-10%, if the air temperature for the burners of the kiln may become between 200°C-250°C. Also, the waste heat recovery systems are found to be applicable for other drying and burning processes of ceramic plants.